Nutrition and hydration issues for combat sport athletes - Hoffman, J. R.; Maresh, C. M. (Strength and Conditioning Journal, 2011)
To optimize performance improvements and to enhance skeletal muscle recovery from high-intensity training, the athlete needs to ensure adequate energy and protein consumption. Protein intake may have even greater relevance during periods of weight loss often associated with the combat sport athlete. Combat sport athletes often use water restriction to accomplish desired weight loss. This has several important performance and physiological implications that pose significant health risks. This paper will focus on several nutritional and hydration strategies and how they specifically relate to combat sports with regard to training and competition.